Population Pharmacokinetic Estimates Suggest Elevated Clearance and Distribution Volume of Desethylamodiaquine in Pediatric Patients with Sickle Cell Disease Treated with Artesunate-Amodiaquine - George O. Adjei, MD, PhD; Seth K. Amponsah, PhD; Bamenla Q. Goka, MB. ChB, MRCP, FWACP; Christabel Enweronu-Laryea, MBBS, MSc, FRCPCH; Lorna Renner, MB. ChB, MPH, FRCPCH, FGCPS; Abdul Malik Sulley, MSc; Michael Alifrangis, MSc, PhD; Jorgen A.L. Kurtzhals, MD, PhD (Elsevier, 2019)
Background: There is limited information on the safety or efficacy of currently recommended antimalarial drugs in patients with sickle cell disease (SCD), a population predisposed to worse outcomes if affected by acute malaria. Artesunate-amodiaquine (ASAQ) is the first-line treatment for uncomplicated malaria (UM) in many malaria-endemic countries and is also used for treatment of UM in SCD patients. There is, however, no information to date, on the pharmacokinetics (PK) of amodiaquine or artesunate or the metabolites of these drugs in SCD patients. Objectives: This study sought to determine the PK of desethylamodiaquine (DEAQ), the main active metabolite of amodiaquine, among paediatric SCD patients with UM treated with artesunate-amodiaquine (ASAQ). Methods: Plasma concentration-time data (median DEAQ levels) of SCD children (n = 16) was initially compared with those of concurrently recruited non-SCD paediatric patients with acute UM (n = 13). A population PK modelling approach was then used to analyze plasma DEAQ concentrations obtained between 64 and 169 hours after oral administration of ASAQ in paediatric SCD patients with acute UM (n = 16). To improve PK modeling, DEAQ concentration-time data (n = 21) from SCD was merged with DEAQ concentration-time data (n = 169) of a historical paediatric population treated with ASAQ (n = 103) from the same study setting. Results: The median DEAQ concentrations on days 3 and 7 were comparatively lower in the SCD patients compared to the non-SCD patients. A two-compartment model best described the plasma DEAQ concentration-time data of the merged data (current SCD data and historical data). The estimated population clearance of DEAQ was higher in the SCD patients (67 L/h, 21% relative standard error (RSE) compared with the non-SCD population (15.5 L/h, 32% RSE). The central volume of distribution was larger in the SCD patients compared with the non-SCD patients (4400 L, 43% RSE vs. 368 L, 34% RSE). Conclusions: The data shows a tendency towards lower DEAQ concentration in SCD patients and the exploratory population PK estimates suggest altered DEAQ disposition in SCD patients with acute UM. These findings, which if confirmed, may reflect pathophysiological changes associated with SCD on DEAQ disposition, have implications for therapeutic response to amodiaquine in SCD patients. The limited number of recruited SCD patients and sparse sampling approach however, limits extrapolation of the data, and calls for further studies in a larger population. Key words: Clearance, Desethylamodiaquine, Sickle cell disease